Active prey selection in developing larvae of Atlantic bluefin tuna (Thunnus thynnus) in spawning grounds of the Gulf of Mexico. (10th April 2021) - Shiroza, Akihiro; Malca, Estrella; Lamkin, John T; Gerard, Trika; Landry, Michael R; Stukel, Michael R; Laiz-Carrión, Raúl; Swalethorp, Rasmus
Abstract: Bluefin tuna spawn in restricted areas of subtropical oligotrophic seas. Here, we investigate the zooplankton prey and feeding selectivity of early larval stages of Atlantic bluefin tuna (ABT, Thunnus thynnus ) in larval rearing habitat of the Gulf of Mexico. Larvae and zooplankton were collected during two multi-day Lagrangian experiments during peak spawning in May 2017 and 2018. Larvae were categorized by flexion stage and standard length. We identified, enumerated and sized zooplankton from larval gut contents and in the ambient community. Ciliates were quantitatively important (up to 9%) in carbon-based diets of early larvae. As larvae grew, diet composition and prey selection shifted from small copepod nauplii and calanoid copepodites to larger podonid cladocerans, which accounted for up to 70% of ingested carbon. Even when cladoceran abundances were <0.2 m −3, they comprised 23% of postflexion stage diet. Feeding behaviors of larvae at different development stages were more specialized, and prey selection narrowed to appendicularians and primarily cladocerans when these taxa were more abundant. Our findings suggest that ABT larvae have the capacity to switch from passive selection, regulated by physical factors, to active selection of presumably energetically optimal prey.